-1=-6m+13

Simple and best practice solution for -1=-6m+13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1=-6m+13 equation:



-1=-6m+13
We move all terms to the left:
-1-(-6m+13)=0
We get rid of parentheses
6m-13-1=0
We add all the numbers together, and all the variables
6m-14=0
We move all terms containing m to the left, all other terms to the right
6m=14
m=14/6
m=2+1/3

See similar equations:

| 7|3x-7|=14 | | 2x-1+x+4+3x+1=22 | | 2(x+4)=2×x+2×4=2x+8 | | -100=n+80 | | 16-p=3p+8-p | | 8(x-2)=6x+4+2x | | 5/x-10=29 | | 3(2c+1)=39-2(c+2) | | 2h+26=50 | | 3(y-2)+15=(2)(18)-3 | | x+7=-49 | | 8(x-1=6x+4+2x | | 5b^2+17b-40=0 | | (h+20)/9=5 | | 16−2t=​2/​3t+9 | | 4x-2+(5x-1=-3(7-x) | | 3x2+17x+20=0 | | 3+4m=15-5m | | (1+x)^12=1.12 | | |5x-6|+7=22 | | 48=3w+12 | | T(n)=2n+7 | | 3q^/6=72 | | 5-(3x+2)+7=2x+1 | | 4.5+1.5=18-3k | | c2–25=0 | | 27=u/2-14 | | 180=28-y | | T=5s+4.83 | | 24=170-x | | 3/4k+3/8k=12 | | -2z+4=-8 |

Equations solver categories